2020
DOI: 10.1177/1747954120961200
|View full text |Cite
|
Sign up to set email alerts
|

Concussion knowledge, attitude and reporting intention in rugby coaches and high school rugby players

Abstract: The aim of this study was to evaluate New Zealand high school rugby union players’ and community coaches’ concussion knowledge (CK), concussion attitude (CA) and concussion reporting intentions (CRI) and to explore the impact gender, age, ethnicity, socio-economic status, experience, and concussion history had on these outcome measures. This cross-sectional study utilised the Rosenbaum Concussion Knowledge and Attitudes survey to evaluate CK, CA and CRI. The survey and demographic information were completed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 84 publications
(128 reference statements)
1
25
1
Order By: Relevance
“…The low referral rate of players to immediate care following a loss of consciousness needs to be addressed in future SARU educational initiatives. 32 The current study indicated that coaches in community rugby have the highest perceived responsibility to uphold post-concussion RTP. Half of the players, coaches and administrative staff identified coaches as responsible in the assessment of whether a player is ready to RTP post-concussion.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The low referral rate of players to immediate care following a loss of consciousness needs to be addressed in future SARU educational initiatives. 32 The current study indicated that coaches in community rugby have the highest perceived responsibility to uphold post-concussion RTP. Half of the players, coaches and administrative staff identified coaches as responsible in the assessment of whether a player is ready to RTP post-concussion.…”
Section: Discussionmentioning
confidence: 66%
“…Half of the players, coaches and administrative staff identified coaches as responsible in the assessment of whether a player is ready to RTP post-concussion. The study by Salmon et al 32 revealed that 71% of high school players surveyed in the study reported that they received concussion information from their coach. Coaches were also the most identified stakeholders responsible for monitoring matches and training for concussions.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations